Analyzing and Designing Public Aspiration Category and Data Information System through Agile Scrum Approach - Azhar, Firyal (International Journal Labs, 2023)
Bappeda Malang City has problems in the implementation of community aspirations data collection which results in difficulty seeing the latest aspirations data and the long flow of data collection. In this case, the authors conducted an analysis and design of a web-based community aspirations data collection system which would make it easier for Bappeda to collect data on aspirations. This web-based aspiration data collection system will make it easier for Bappeda to see the actual aspirations conveyed by the community. The method in analyzing and designing a web-based data collection and categorization system with the Laravel 9 framework uses the scrum method with various customized activities. The process of activities carried out to produce the aspirational data collection system included condition analysis and data collection, system design, and system implementation. The process in this study goes through the stages of system design, which includes scrum (product backlog, sprints, scrum meetings) and also business design (flowchart diagrams, use case diagrams, ERD diagrams). The results obtained in this study are of good value and can be used after carrying out user testing carried out at the system implementation stage.